MODELISASI HANDLE PINTU DENGAN PENGGABUNGAN KURVA BEZIER DAN HASIL DEFORMASI TABUNG - Wahana, Nadhilah Putri; Juliyanto, Bagus; Ubaidillah, Firdaus (Jurusan Matematika FMIPA Universitas Jember, 2020)
Door handles are one of the important parts of a door that is used as a handle when closing or opening the door. Door handles are divided into three parts, which are the body part, the leg part, and the footgear part. The study was designed to model the shapes of the door handles using the Bezier curve method, dilatation deformation, and translation deformation, so that the shapes of the door handle become more various and symmetrical. The method of this study was divided into several steps. First, the body part, the leg part, and the footgear part of the door handles were modeled. Then, the model of the every part of the door handles from the previous step were combined. The results of this study were modelling the door handles.Keywords: Bezier curve, dilatation, door handle, translation.